The last empress of France : the rebellious life of Eugénie De Montijo - Kladstrup, Petie; Resnick, Evelyne (Hanover Square Press, 2025)
"Although a nineteenth-century woman, her almost twenty-first century outlook was key to the creation of modern France. Viewed frequently as a mere "ornament of the throne" of her husband, Emperor Napoleon III, this Spanish-born aristocrat proved to be almost as fiery as her red hair, fighting against institutional limitations, establishing innovations in childcare and women's health, scientific research and education, battling anti-Semitism and "sex prejudice," all the while displaying a political acumen so sharp that her husband gave her sole control of the government during his absences and consulted her daily when he was home. But the triumphs and glamour of her life were coupled with heartbreak and tragedy"--